Development of E-Module for Mathematics Learning for Junior High School Students Based on Local Culture at the Van der Wijck Fort Complex to Improve Students’ Mathematical Reasoning Ability and Learning Interest - Nurul Hidayah; Jailani Jailani (International Journal of Science and Mathematics Education, 2025)
This study aims to develop a junior high school mathematics e-module based on local culture at the Van der Wijck Fortress complex to enhance students’ mathematical reasoning skills and learning interest. Specifically, the objectives are: (1) to describe the characteristics of the local culture-based e-module that can improve reasoning ability and learning motivation, and (2) to produce a high-quality e-module that meets the criteria of validity, practicality, and effectiveness. The research employed the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The participants consisted of one teacher, 31 students in the experimental class, and 32 students in the control class at a public junior high school in Kebumen Regency. The instruments used included validation sheets for media and material, competency tests, mathematical reasoning tests, learning interest questionnaires, and practicality assessment forms for teachers and students. The results showed that the e-module possesses characteristics of being self-instructional, self-contained, stand-alone, adaptive, and user-friendly. Product validity was confirmed through expert validation with average scores of 4.26 for media and 4.35 for material (very valid). The validation of instruments obtained average scores ranging from 4.5 to 4.92, categorized as very valid. Practicality was demonstrated through teacher assessments of 92%, student assessments of 85%, and learning implementation of 94% (all very practical). Effectiveness testing using the Multivariate Hotelling’s T² test indicated significant differences between experimental and control classes in competency test scores, mathematical reasoning, and learning interest. Therefore, the local culture-based mathematics e-module is proven valid, practical, and effective in enhancing students’ mathematical reasoning and learning motivation.